A micro-nano particle reinforced aluminum wire based on electroplasticity and a preparation method thereof

By introducing electroplastic and micro-nano-grade particles into the aluminum base wire and adopting a specific preparation process, the problems of cracks and joint weakening in aluminum alloy welding are solved, and the weld strength is improved and the crack sensitivity is reduced.

CN116334459BActive Publication Date: 2025-02-28SHANDONG SHISHANG WELDING MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310269478.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-15
Publication Date
2025-02-28
Estimated Expiration
2043-03-15

AI Technical Summary

Technical Problem

There are problems such as cracks and joint weakening in the existing aluminum alloy welding process, resulting in low weld strength and high crack sensitivity.

Method used

The aluminum baseline material based on electroplasticity is used to enhance the electroplastic aluminum baseline, and is prepared by continuous semi-solid rheological extrusion technology and multiple drawing processes, combined with pulse currents of specific frequencies and sizes for extraction to generate TiB2 and TiC micro-nanoscale second phase particles.

Benefits of technology

It reduces the problem of cracks and joint weakening during welding and additive processes, improves weld strength, reduces crack sensitivity, and improves the plasticity and tissue uniformity of the wire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004134251830000011
    Figure HDA0004134251830000011
  • Figure HDA0004134251830000021
    Figure HDA0004134251830000021
  • Figure HDA0004134251830000022
    Figure HDA0004134251830000022
Patent Text Reader

Abstract

A micro-nano particle reinforced aluminum wire based on electroplasticity and a preparation method thereof, relating to the technical field of aluminum-based wires, the wire containing TiB 2 , TiC reinforced particles, its weight percentage is; 7.5-11.2wt.% Zn, 2.08-2.73wt.% Mg, 2.15-2.30wt.% Cu, 0.1-0.5wt.% Si, 0.1-0.12wt.% Zr, 0.5-7wt.% Ti, 0.25-2.1wt.% B, 0.5-2wt.% C, 1.25-15wt.% K, 0.05-0.2wt.% F, the balance is Al. The aluminum-based material is melted, and then the aluminum-based blank is prepared by continuous semi-solid rheological extrusion technology, and then it undergoes multiple drawing processes, and a current of specific size and frequency is passed through different drawing processes, and subsequent surface treatment is performed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum-based wire materials, and in particular to a micro-nano particle-reinforced aluminum-based wire material based on electroplasticity and a preparation method thereof. Background Art

[0002] Aluminum alloy is an alloy formed by adding alloying elements to pure aluminum materials. The addition of alloying elements improves the performance of pure aluminum, making it widely used in various industries. Aluminum alloy has the characteristics of light material, high strength, good thermal conductivity, and good processing performance. Compared with stainless steel materials, it can be better used in industries such as automobile manufacturing and aerospace manufacturing. Due to the addition of alloying elements and different heat treatment processes, there are many kinds of aluminum alloys. Among them, high-strength aluminum alloy refers to aluminum alloys with a certain amount of chromium, zinc, magnesium and other elements added. These elements improve the tensile strength and yield strength of aluminum alloys by affecting grain nucleation and dendrite growth. However, aluminum alloys also have the characteristics of high relative content of alloying elements, mushy solidification and severe element segregation. High-strength aluminum alloys are generally used in industrial production in the form of structural parts because high-strength aluminum alloys have poor welding performance.

[0003] Common welding processes for aluminum alloys include arc welding, solid phase welding, laser welding, etc. Among them, gas metal arc welding (MIG) is the most commonly used welding process for aluminum alloys, with the advantages of high productivity and good weld formation. Stir friction welding is also a common aluminum alloy welding method, which has the advantages of small changes in heat-affected zone structure and low residual stress, but it also has obvious disadvantages. These disadvantages make it inferior to MIG in practical applications. Laser welding of aluminum alloys has low heat and fast speed, and the solidification speed is fast during welding, resulting in more defects such as pores and cracks. There are two main types of defects in the additive manufacturing of metals: pores and cracks. Solving the defects of welding processes can start from improved fusion welding and additives. Therefore, it is necessary to reasonably match welding materials or wires to avoid various problems that occur during welding. Summary of the invention

[0004] The present invention proposes a micro-nano particle reinforced aluminum wire based on electroplasticity and a preparation method thereof. The use of the wire can reduce problems such as cracks and joint weakening that occur during welding and material addition, improve weld strength, and reduce weld crack sensitivity. The use of the manufacturing method can improve the plasticity of the wire while ensuring wire production efficiency, reduce defects inside the wire, make the structure inside the wire uniform, and generate reinforced particles that are evenly dispersed in the wire.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] In the technical solution of the first aspect: the proposed micro-nano particle reinforced aluminum wire wire based on electroplasticity contains Ti B2 and TiC strengthening particles, and the weight percentage of the raw material elements of the micro-nano particle reinforced aluminum wire wire is: 7.5-11.2wt.% Zn, 2.08-2.73wt.% Mg, 2.15-2.30wt.% Cu, 0.1-0.5wt.% Si, 0.1-0.12wt.% Zr, 0.5-7wt.% Ti, 0.25-5.3wt.% B, 0.5-2wt.% C, 1.25-15wt.% K, 0.05-0.2wt.% F, and the balance is Al.

[0007] In the second aspect of the technical solution: a new aluminum wire preparation solution is proposed. The aluminum-based material is melted, and then the aluminum wire blank is prepared by continuous semi-solid rheological extrusion technology, and then it undergoes multiple drawing processes, and a current of specific size and frequency is passed during different drawing processes; the order of drawing the plate is to first draw once, and the shrinkage rate of the first drawing is 30-40%, then draw twice, and the shrinkage rate of the second drawing is 40-50%, and finally draw three times, and the shrinkage rate of the third drawing is 70%-80%. After drawing to 1.2mm, subsequent surface treatment and winding are carried out; the shrinkage rate refers to the ratio of the cross-sectional diameter of the wire after shrinkage to the original cross-sectional diameter. For example, a shrinkage rate of 80% means that the cross-sectional diameter of the wire becomes 80% of the original. The specific steps are as follows:

[0008] S1: Pure aluminum is melted at 700-800°C in a smelting furnace, and then K2TiF4 and KBF4 mixed salt, copper particles, Al-Si master alloy, magnesium particles, zinc particles, and graphite powder are added in sequence, and Al-Zr alloy extruded into 10mm wire is inserted into the aluminum melt at 10mm / min, and then the melt purification operation is performed.

[0009] S2: The aluminum melt prepared in S1 is cooled to 750°C for heat preservation, and injected into a continuous rheological extruder at 640°C-735°C to prepare an aluminum wire having a diameter of 10-12 mm.

[0010] S3: The aluminum wire is drawn, and a unidirectional continuous pulse current is introduced into the wire through two flexible conductive clamps. First, a drawing is performed. During the drawing process, an average current of 40-50A, a pulse width of 30ms, an interval of 10ms, and a frequency of 50Hz are introduced. The shrinkage rate of the first drawing is 30%-40%. Then a second drawing is performed. During the second drawing process, an average current of 30-40A, a pulse width of 20ms, an interval of 10ms, and a frequency of 50Hz are introduced. The shrinkage rate of the second drawing is 40%-50%. Then a third drawing is performed. The shrinkage rate of the third drawing is 70-80%. During the third drawing process, an average current of 20-30A, a pulse width of 10ms, an interval of 10ms, and a frequency of 50Hz are introduced to improve the elongation of the wire and ensure the efficiency of wire drawing. The above-mentioned pulse currents are all unidirectional and in the same direction as the aluminum wire.

[0011] S4: The wire obtained in step S3 is further scraped and subjected to other surface treatments used for winding and coiled to obtain a wire with a smooth surface, good wire feedability and high performance.

[0012] The technical solution of the third aspect: a flexible conductive clamp based on electroplasticity is invented, including a copper square shell with a U-shaped cross-section, a plurality of copper cylinders are arranged on the inner surface of the copper square shell in the U-shaped cavity, the plurality of copper cylinders form a copper brush, the end face of the entire copper brush forms a semi-cylindrical cavity, the two copper square shells are interlocked, and the wire is clamped in the semi-cylindrical cavity. The copper square shell contains 140-200 copper brushes, 70-100 on one side. The copper cylinder and the copper square shell are fixedly connected by a spring, and shrink into the copper square shell as the size of the wire in the clamp. The distance between the two flexible clamps is limited to 60-90cm. Flexible conductive clamps are respectively arranged at both ends of the aluminum base wire to clamp the aluminum base wire. Current is passed through the conductive clamp.

[0013] Compared with the current technology, the micro-nano particle reinforced aluminum wire based on electroplasticity and the preparation method thereof proposed in the present invention have the following advantages and beneficial effects.

[0014] (1) Pulse current of a specific frequency and size is added during the drawing process to produce an electroplastic effect. This solves the problems of high deformation resistance and low plasticity of high-strength aluminum-based wires and low elongation and easy cracking during the drawing process in the traditional drawing process. The drawn wire is free of cracks, with a smooth surface and more uniform thickness, and does not require the intermediate annealing process of traditional drawing. Moreover, under the same drawing conditions as traditional drawing (drawing rate and drawing force), electroplasticity reduces the critical shrinkage rate of the wire without cracks, thereby reducing the cracking tendency of the wire.

[0015] (2) TiB2 and TiC micro- and nano-scale second phase particles are generated by in-situ synthesis during wire drawing. The addition of pulse current promotes changes in material structure and the generation of micro- and nano-scale second phase particles. During welding, the wire manufactured by the present invention injects micro- and nano-scale second phase particles into the high-temperature molten pool, which promotes the heterogeneous nucleation effect and refines the solidification structure. At the same time, it also promotes the release of local tensile stress formed in the micro-area thermal processing engineering, thereby suppressing welding cracks that are very easy to occur in traditional welding and additive manufacturing.

[0016] (3) The comprehensive performance of welded and additively treated high-strength aluminum alloy samples was improved. The addition of micro- and nano-scale particles refined the matrix structure of the sample and thus improved the strength of the alloy. TiC and TiB2 particles had a synergistic strengthening effect, and the addition of TiC particles increased the hardness of the sample and improved the wear resistance of the sample.

[0017] (4) A flexible conductive clamp based on electroplasticity was invented. The clamp fits on the surface of the wire, is adaptable to wires of various sizes, has good conductivity, reduces the shaking of the wire during the wire drawing process, is low in cost and has strong applicability. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The present invention is a flow chart for preparing an aluminum wire.

[0019] Figure 2 This is an overall schematic diagram of a flexible conductive clamp based on electroplasticity of the present invention.

[0020] Figure 3 This is a schematic diagram of a single side of a flexible conductive clamp based on electroplasticity of the present invention.

[0021] Markings in the figure: 1. clamp; 2. wire.

[0022] 3. Copper brush; 4. Copper shell. DETAILED DESCRIPTION

[0023] The following examples further illustrate the technical means, inventive features and implementation advantages of the present invention.

[0024] Example 1

[0025] A micro-nano particle reinforced aluminum wire based on electroplasticity, the weight percentage of the wire comprises the following elements: 8.2wt% Zn, 2.12wt% Mg, 2.15wt% Cu, 0.2wt% Si, 0.1wt% Zr, 5.2wt% Ti, 4.2wt% B, 1.5wt% C, 14.5wt.% K, 0.05wt.% F, and the balance is Al.

[0026] The preparation method of the micro-nano particle reinforced aluminum wire based on electroplasticity of Example 1 comprises the following specific steps:

[0027] S1: Pure aluminum was melted at 750°C in a smelting furnace, and then K2TiF4 and KBF4 mixed salt, copper particles, Al-Si master alloy, magnesium particles, zinc particles, and graphite powder were added in sequence, and Al-Zr alloy extruded into 10 mm wire was inserted into the aluminum melt at 10 mm / min, and then the melt purification operation was performed.

[0028] S2: The aluminum melt prepared in S1 is cooled to about 750°C for heat preservation, and injected into a continuous rheological extruder at 660°C to prepare an aluminum base wire with a diameter of 10 mm.

[0029] S3: The aluminum wire is drawn, and a unidirectional continuous pulse current is introduced into the wire through two flexible conductive clamps. First, a drawing is performed, and a pulse current with an average current of 50A, a pulse width of 30ms, a pulse interval of 10ms, and a frequency of 50Hz is introduced. The shrinkage rate of the first drawing is 30%, and then a second drawing is performed. During the second drawing process, a pulse current with an average current of 30A, a pulse width of 20ms, a pulse interval of 10ms, and a frequency of 50Hz is introduced. The shrinkage rate of the second drawing is 50%, and then a third drawing is performed. During the third drawing process, a pulse current with an average current of 20A, a pulse width of 10ms, a pulse interval of 10ms, and a frequency of 50Hz is introduced to improve the plasticity and elongation of the wire. The shrinkage rate of the third drawing is 80%, and finally it is drawn into a 1.2mm wire.

[0030] S4: The wire obtained in step S3 is further scraped and subjected to other surface treatments used for wire winding and coiled to obtain a particle-reinforced aluminum wire with a smooth surface, good wire feedability and high performance.

[0031] The manufactured wire has good wire feedability and a tensile strength of 131Mpa. The wire is used to weld 7075 aluminum alloy, and the strength of the welded joint is 335Mpa after heat treatment (aging at 180℃×2 hours). The plasticity is improved during the drawing process, and the critical shrinkage rate without cracks can reach 30% for the first drawing, 50% for the second drawing, and 80% for the third drawing.

[0032] Example 2

[0033] A micro-nano particle reinforced aluminum wire based on electroplasticity, the weight percentage of the wire comprises the following elements: 9wt% Zn, 2.08wt% Mg, 2.2wt% Cu, 0.1wt% Si, 0.1wt% Zr, 3.5wt% Ti, 3wt% B, 2wt% C, 10wt.% K, 0.07wt.% F, and the balance is Al.

[0034] The preparation method of the micro-nano particle reinforced aluminum wire based on electroplasticity of Example 2 comprises the following specific steps:

[0035] S1: Pure aluminum was melted at 800°C in a smelting furnace, and then K2TiF4 and KBF4 mixed salt, copper particles, Al-Si master alloy, magnesium particles, zinc particles, and graphite powder were added in sequence, and Al-Zr alloy extruded into 10 mm wire was inserted into the aluminum melt at 10 mm / min, and then the melt purification operation was performed.

[0036] S2: The aluminum melt prepared in S1 is cooled to about 750°C for heat preservation, and injected into a continuous rheological extruder at 680°C to prepare an aluminum base wire with a diameter of 12 mm.

[0037] S3: The aluminum wire is drawn, and a unidirectional continuous pulse current is introduced into the wire through two flexible conductive clamps. First, a drawing is performed, and a pulse current with an average current of 40A, a pulse width of 3ms, a pulse interval of 10ms, and a frequency of 50Hz is introduced. The shrinkage rate of the first drawing is 33%, and then a second drawing is performed. During the second drawing process, a pulse current with an average current of 40A, a pulse width of 20ms, a pulse interval of 10ms, and a frequency of 50Hz is introduced. The shrinkage rate of the second drawing is 43%, and then a third drawing is performed. During the third drawing process, a pulse current with an average current of 30A, a pulse width of 10ms, a pulse interval of 10ms, and a frequency of 50Hz is introduced to improve the plasticity and elongation of the wire. The shrinkage rate of the third drawing is 70%, and finally it is drawn into a 1.2mm wire.

[0038] S4: The wire obtained in step S3 is further scraped and subjected to other surface treatments and wound into a coil to obtain a particle-reinforced aluminum wire with a smooth surface, good wire feedability and high performance.

[0039] The manufactured wire has good wire feedability and a tensile strength of 129Mpa. The wire is used to weld 7075 aluminum alloy, and the strength of the welded joint is 325Mpa after heat treatment (aging at 180℃×2 hours). The plasticity is improved during the drawing process, and the critical shrinkage rate without cracks can reach 33% for the first drawing, 43% for the second drawing, and 70% for the third drawing.

[0040] Example 3

[0041] A micro-nano particle reinforced aluminum wire based on electroplasticity, the weight percentage of the wire comprises the following elements: 10wt% Zn, 2.33wt% Mg, 2.30wt% Cu, 0.5wt% Si, 0.1wt% Zr, 2.9wt% Ti, 4.8wt% B, 0.5wt% C, 7.5wt.% K, 0.05wt.% F, and the balance is Al.

[0042] The preparation method of the micro-nano particle reinforced aluminum wire based on electroplasticity of Example 3 comprises the following specific steps:

[0043] S1: Pure aluminum was melted at 780°C in a smelting furnace, and then K2TiF4 and KBF4 mixed salt, copper particles, Al-Si master alloy, magnesium particles, zinc particles, and graphite powder were added in sequence, and Al-Zr alloy extruded into 10 mm wire was inserted into the aluminum melt at 10 mm / min, and then the melt purification operation was performed.

[0044] S2: The aluminum melt prepared in S1 is cooled to about 750°C for heat preservation, and injected into a continuous rheological extruder at 735°C to prepare an aluminum wire having a diameter of 10 mm.

[0045] S3: The aluminum wire is drawn, and a unidirectional continuous pulse current is introduced into the wire through two flexible conductive clamps. First, a drawing is performed, and a pulse current with an average current of 45A, a pulse width of 30ms, a pulse interval of 10ms, and a frequency of 50Hz is introduced. The shrinkage rate of the first drawing is 40%, and then a second drawing is performed. During the second drawing process, a pulse current with an average current of 35A, a pulse width of 20ms, a pulse interval of 10ms, and a frequency of 50Hz is introduced. The shrinkage rate of the second drawing is 40%, and then a third drawing is performed. During the third drawing process, a pulse current with an average current of 25A, a pulse width of 10ms, a pulse interval of 10ms, and a frequency of 50Hz is introduced to increase the elongation of the wire and ensure the efficiency of wire drawing. The shrinkage rate of the third drawing is about 75%, and finally it is drawn into a 1.2mm wire.

[0046] S4: The wire obtained in step S3 is further scraped and subjected to other surface treatments and wound into a coil to obtain a particle-reinforced aluminum wire with a smooth surface, good wire feedability and high performance.

[0047] The manufactured wire has good wire feedability and a tensile strength of 135Mpa. The wire is used to weld 7075 aluminum alloy, and the strength of the welded joint is 347Mpa after heat treatment (aging at 180℃×2 hours). The plasticity is improved during the drawing process, and the critical shrinkage rate without cracks can reach 40% for the first drawing, 40% for the second drawing, and 75% for the third drawing.

[0048] It should be noted that the above are only specific implementation methods with better comparative effects in the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, and they should all be covered by the protection scope of the present invention.

Claims

1. A method for preparing a micro-nano particle reinforced aluminum wire based on electroplasticity, characterized in that: The aluminum wire wire contains TiB2 and TiC strengthening particles, and the weight percentage of the micro-nano particle reinforced aluminum wire wire is: 7.5-11.2wt.% Zn, 2.08-2.73wt.% Mg, 2.15-2.30wt.% Cu, 0.1-0.5wt.% Si, 0.1-0.12wt.% Zr, 0.5-7wt.% Ti, 0.25-5.3wt.% B, 0.5-2wt.% C, 1.25-15wt.% K, 0.05-0.2wt.% F, and the balance is Al; The specific steps are as follows: S1: pure aluminum is melted at 700-800°C in a smelting furnace, and then K2TiF4 and KBF4 mixed salt, copper particles, Al-Si master alloy, magnesium particles, zinc particles, and graphite powder are added in sequence, and Al-Zr alloy extruded into 10 mm wire is inserted into the aluminum melt at 10 mm / min, and then the melt purification operation is performed; S2: cooling the aluminum melt prepared in S1 to 750°C for heat preservation, and injecting it into a continuous rheological extruder at 640°C-735°C to prepare an aluminum base wire with a diameter of 10-12 mm; S3: Drawing the aluminum wire, introducing a unidirectional continuous pulse current into the wire through two flexible conductive clamps; firstly, drawing is performed once, during which an average current of 40-50A, a pulse width of 30ms, an interval of 10ms, and a frequency of 50Hz are introduced, and the shrinkage rate of the first drawing is 30%-40%, then a second drawing is performed, during which an average current of 30-40A, a pulse width of 20ms, an interval of 10ms, and a frequency of 50Hz are introduced, and the shrinkage rate of the second drawing is 40%-50%, then a third drawing is performed, and the shrinkage rate of the third drawing is 70-80%, during which an average current of 20-30A, a pulse width of 10ms, an interval of 10ms, and a frequency of 50Hz are introduced, so as to improve the elongation of the wire and ensure the efficiency of wire drawing; the above-mentioned pulse currents are all unidirectional and in the same direction as the aluminum wire; S4: The wire obtained in step S3 is further scraped and subjected to other surface treatments used for winding and coiled to obtain a wire with a smooth surface, good wire feedability and high performance.

2. The method according to claim 1, characterized in that A flexible conductive clamp is used for fixing, including a copper square shell with a U-shaped cross-section, a plurality of copper cylinders are arranged on the inner surface of the copper square shell in the U-shaped cavity, the plurality of copper cylinders form a copper brush, the end surface of the entire copper brush forms a semi-cylindrical cavity, the two copper square shells are interlocked, and the wire is clamped in the semi-cylindrical cavity; the copper cylinder and the copper square shell are fixedly connected by a spring, and shrink into the copper square shell according to the size of the wire in the clamp.

3. The method according to claim 1, characterized in that The copper square housing contains 140-200 copper brushes, 70-100 on each side.

Citation Information

Patent Citations

  • 7-series aluminum alloy profile and preparation method thereof

    CN109295332A

  • In-situ nanometer reinforced aluminum alloy for lightweight automobile anti-collision beam and preparation method

    CN109504870A